2017
DOI: 10.1016/j.ijimpeng.2017.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Strain rate dependence of mode II delamination resistance in through thickness reinforced laminated composites

Abstract: A thorough experimental procedure is presented in which the mode II delamination resistance of a laminated fibre reinforced plastic (FRP) composite with and without Zpins is characterised when subjected to increasing strain rates. Standard three-point End Notched Flexure (3ENF) specimens were subjected to increasing displacement loading rates from quasi-static (~0m/s) to high velocity impact (5m/s) using a range of test equipment including drop weight impact tower and a Modified Hopkinson Bar apparatus for dyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 42 publications
3
25
1
Order By: Relevance
“…The TTR effectiveness in resisting crack propagation is not significant until the shear displacement reach about 0.1 mm, therefore , the crack had propagated for a considerable distance before considerable delamination retardation effect of the Z-pin kicked in. The effectiveness of Z-pins in dynamic shear delamination observed in the tests presented here was much lower than what previously reported [16]. This could be due to the fact that no precracking from the PTFE film [30] was performed.…”
Section: Crack Growth Ratecontrasting
confidence: 67%
See 2 more Smart Citations
“…The TTR effectiveness in resisting crack propagation is not significant until the shear displacement reach about 0.1 mm, therefore , the crack had propagated for a considerable distance before considerable delamination retardation effect of the Z-pin kicked in. The effectiveness of Z-pins in dynamic shear delamination observed in the tests presented here was much lower than what previously reported [16]. This could be due to the fact that no precracking from the PTFE film [30] was performed.…”
Section: Crack Growth Ratecontrasting
confidence: 67%
“…However, despite the fact that Z-pinning has been employed for improving impact-damage resistance, the resulting dynamic effects are still not fully understood. Recently, ENF tests have been conducted at displacement rates up to 5m/s [16]. It was reported that the delamination resistance at the moment of crack initiation was significantly improved with Z-pinning, and this effect became more pronounced as the loading rate was increased.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Z-pins were split in quasi-static tests, while no significant splitting was found in dynamic test samples. With the increase in mixed mode ratio, the Z-pins were ruptured at a position closer to the mid-plane, leading to lower pull-out lengths [29]. The energy dissipation during the failure of Z-pins decreased with mode mix ratio, mainly due to the pin rupture and reduced energy dissipation during frictional pull-out stage.…”
Section: Failure Mechanismsmentioning
confidence: 98%
“…Many composite structures may be threatened by impact loading [20], and comprehensive understanding about the dynamic property of Z-pinned laminates is vital for the design and analysis of such structures [12,13,21]. To the authors' knowledge, there is no research reported addressing the dynamic in-plane failure process of Z-pinned composites yet.…”
Section: Introductionmentioning
confidence: 99%